Natural and anthropogenic factors controlling organic carbon storage in riverine wetlands along South Korea’s four rivers - Sang-Leen Yun; Terrence A. McCloskey; Marcelo C. L. Cohen; Kam-biu Liu; Hae-Seon Shin; Junghyung Ryu (Scientific Reports)
Abstract This study explores carbon sequestration in South Korea’s riverine wetlands, focusing on the four major rivers: Han, Yeongsan, Geum, and Nakdong. Field data from the Yeongsan River wetland, including 3D topography surveys, grainsize analyses, and loss-on-ignition measurements, were used to assess carbon stocks and their environmental drivers. The Yeongsan River was selected as a representative site due to its geomorphological, hydrological, and climatic similarities with the other three major rivers, which influence sediment transport and carbon dynamics. Carbon stocks of 3.31 megagrams (Mg) per hectare, observed in the Dam-Yang Stream Wetland, suggest that the four major rivers collectively have the potential to store approximately 23.42 million metric tons of carbon annually, accounting for 3.9% of South Korea’s carbon budget. Geomorphological features at different elevations significantly influence soil carbon storage, with finer sediments contributing to higher carbon retention in low-energy environments. Seasonal variations in stream geomorphology, driven by floods and tropical cyclones, are dominant factors regulating sediment transport and organic matter deposition. Our findings suggest that controlled discharge events could enhance sediment and organic material retention, boosting carbon sequestration across riverine wetlands. This study highlights the critical role of geomorphological and hydrological processes in enhancing wetland carbon storage and mitigating carbon emissions.